An Analysis of the Influence of Capital Expenditures, Social Aids Expenditures, OUR, HDI, and Education Level on Absolute Poverty in East Java for the 2015–2024 Period - Roswandi, Muhammad Syawaludin Thariq; Susilo (Journal of Development Economic and Social Studies, 2026)
Absolute poverty in East Java Province remains a structural problem influenced by development disparities, labor market conditions, and the quality of human development, with a slower rate of poverty reduction compared to the national average. This study aims to examine the influence of independent variables, namely capital expenditures, social aids expenditures, open unemployment rate (OUR), Human Development Index (HDI), and education level (proxied by average years of schooling) on absolute poverty in regencies and cities in East Java during the 2015–2024 period. The study employs a quantitative approach using panel data from 38 regencies and cities, analyzed via panel data regression. The results indicate that social aids expenditures, HDI, and education level contribute to reducing absolute poverty, while OUR increases absolute poverty. Meanwhile, lagged capital expenditures does not show a strong short-term contribution to poverty reduction.